1984
DOI: 10.1104/pp.75.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Conjugation by Tobacco Mesophyll Protoplasts

Abstract: Auxin induction of the proliferation of Nicotiana tabacum (cv Xanthi) mesophyll protoplasts and of protoplast-derived cells was studied. The growth-promoting properties and cytotoxicities at high concentrations of IAA and naphthaleneacetic acid were strongly affected by cell density. The induction of growth by 2,4-dichlorophenoxyacetic acid and picloram was not affected by cell density. The comparison of catabolism of these "'Cllabeled auxins by protoplasts showed that IAA and naphthaleneacetic acid were rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Previous work in our laboratory on auxin metabolism described the synthesis of NAA-L-aspartic acid by tobacco protoplasts (10 There is probably no general explanation for the basis ofamino acid toxicity under low density growth conditions. Previous work in our laboratory on valine toxicity has shown that this amino acid was mainly interfering with the biosynthesis of a related amino acid, isoleucine (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in our laboratory on auxin metabolism described the synthesis of NAA-L-aspartic acid by tobacco protoplasts (10 There is probably no general explanation for the basis ofamino acid toxicity under low density growth conditions. Previous work in our laboratory on valine toxicity has shown that this amino acid was mainly interfering with the biosynthesis of a related amino acid, isoleucine (5).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were rather tedious to perform at high densities since they required serial countings of colony development under the microscope, and since they had to be performed during short periods of time due to the rapid decrease of NAA concentration in the culture medium promoted by the conjugation processes taking place in the cells (10). These observations allowed us, however, to perform biochemical studies under high density growth conditions, which generally required large amounts of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…one-half of the esters are the conjugates of IAA and cellulosic glucans (Piskornik and Bandurski 1972). The ester conjugates seem to predominate among monocotyledon plants (maize, rice), though their synthesis has also been found in Arabidopsis (Tam et al 2000), immature bean seeds (Bialek and Cohen 1989;Jakubowska and Kowalczyk 2004), Scots pine seeds (Ljung et al 2001), tomato pericarp (Catalá et al 1992), henbane cells (Oetiker and Aeschbacher 1997) or tobacco leaf protoplasts (Caboche et al 1984;Delbarre et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…studies (7). A genetic approach to the study ofauxin action could help in understanding this process ofauxin-mediated cell killing.…”
mentioning
confidence: 99%